THE EFFECT OF JOB CHARACTERISTICS, EMPLOYEE EMPOWERMENT AND COMPENSATION ON PERFORMANCE ON CUSTOMER SERVICES OF BANK MANDIRI JEMBER BRANCH - Indah Susanti; Muhammad Firdaus; Yuniorita Indah Handayani (MBA - Journal of Management and Business Aplication, 2021)
This study aims to determine the effect of job characteristics, employee empowerment andcompensation on employee performance at Bank Mandiri Jember Branch. The population in thisstudy were all employees of PT. Bank Mandiri Tbk totaling 162 people. The sample in this studyamounted to 41 respondents. The sampling technique used in this study is a non-probabilitysampling technique, namely the Accidental Sampling approach. The data analysis method used ismultiple linear regression analysis. The results of this study indicate that the variables of jobcharacteristics, employee empowerment and compensation have a simultaneous effect onemployee performance at Bank Mandiri Jember Branch. Partially, these results also show thatthe variables of employee empowerment and compensation have a significant effect on employeeperformance. While the variable of job characteristics has no significant effect on theperformance of employees of Bank Mandiri Jember Branch.Keywords: Job Characteristics, Employee Empowerment, Compensation, Performance